The Impact Law Number 16 of 2019 about Marriage Age Dispensation on The Child Marriage Gap - Amrin Nurfieni (Jember: Sharia Faculty State Islamic University of Kiai Haji Achmad Siddiq Jember, 2023)
Child marriage in Indonesia is quite high. Child marriage is a form of violence against children and is a practice that violates children's basic rights as outlined in the Convention on the Rights of the Child (CRC). Child marriage limits access to essential services, including education and health services, and can have long-term negative impacts on children's well-being and life chances. The legal age limit for marriage in Indonesia is a minimum of 19 years. However, one of the policies in the Marriage Law is a loophole that supports the legality of child marriages, through the granting of dispensations by the Court. The number of requests for marriage dispensation at the Ambarawa Religious Court continues to increase. This data is a reference for the author in studying the impact of the enactment of Law Number 16 of 2019, an amendment to Law Number 1 of 1974 concerning Marriage, on children. This research uses normative juridical methodology, namely reviewing court decisions. As a finding, one of the impacts of the enactment of Law Number 16 of 2019 which amends Law Number 1 of 1974 concerning Marriage is the increase in the number of requests for marriage dispensation at the Ambarawa District Court, Semarang Regency. This increase reached 337%, with the average number of applications per month increasing from 7.44 to 25.07. Changes in the marriage age as stated in Article 7 regarding the minimum marriage age of 19 years are not effective in reducing the number of child marriages. So it is necessary to optimize the implementation of Supreme Court Regulation Number 5 of 2019 concerning Guidelines for Granting Marriage Dispensations to ensure that judges have clear procedures and structured steps in adjudicating marriage dispensation cases.